The effect of inhaled budesonide on adrenal and growth suppression in asthmatic children - Priftis, Kostas N.; Papadimitriou, Anastasios; Gatsopoulou, Evi; Fretzayas, Andrew M.; Nicolaidou, Polyxeni; Yiallouros, Panayiotis K. (My University, 2006)
The present authors evaluated adrenal reserve in asthmatic children on long-term inhaled corticosteroids and whether possible adrenal suppression could be predicted by growth retardation. Low-dose synacthen test (0.5 μg·1.73 m-2) was performed in 72 asthmatic children with a median age of 9.4 (range 4.2-15.7) yrs on long-term treatment (median 18 (range 6-84) months) with low-to-moderate doses (median 363 (range 127-1012) μg·m-2) of inhaled budesonide, as well as in 30 controls. Adrenal suppression was considered as a peak serum cortisol <495 nmol·L-1. The current authors calculated height standard deviation score (HSDS) at the time of testing and height velocity SDS (HVSDS) in the preceding year. Mean HSDS was 0.06±1.3 and HVSDS was -0.9±2.3. Adrenal suppression was disclosed in 15 asthmatic children (20.8%). There were no differences in HSDS and HVSDS between children with and without adrenal suppression. There was no correlation between peak cortisol response and dose or duration of treatment. However, a positive relationship between HVSDS and duration of treatment was noted. These data suggest that long-term treatment of asthmatic children with low and moderate doses of inhaled budesonide may result in mild adrenal suppression that cannot be predicted by growth deceleration. The negative influence of inhaled corticosteroids on growth becomes less the longer the duration of treatment.
Keywords: Adrenal function; Asthma; Children; Growth; Inhaled budesonide